Pembelajaran Picture and Picture Berbasis Modul Resitasi Terhadap Retensi Mahasiswa - Mukarramah Mukarramah; Muhibbuddin Muhibbuddin; Hasanuddin Hasanuddin (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to determine the increase in student learning retention in the human skeletal system material through the application of the Picture and Picture (PAP) learning model based on the recitation module. This study uses an experimental method using a pretest posttest control group design. The population in this study were all 6th semester students. There were 132 students. The sample in this study consisted of 60 students who were randomly selected. The instrument in this study used a recitation-based module and a test device in the form of cognitive questions. The data analysis technique for student learning retention uses the formula recognition methods. The results showed that the retention of the experimental class with the percentage of the first retest 80.20%, the second retest 92.50% and the third retest 101.24% had a very good category compared to the control class, the percentage of the first retest was 83.49%, the second retest was 72.24% and the third retest was 79.50% with a good category. Thus, the application of the PAP learning model based on the recitation module can increase student learning retention on the material of the human skeletal system